2022
DOI: 10.3389/fpubh.2021.790544
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Mycobacterium tuberculosis and Implications for Using Whole-Genome Sequencing for Investigating Recent Tuberculosis Transmission

Abstract: Tuberculosis (TB) control programs use whole-genome sequencing (WGS) of Mycobacterium tuberculosis (Mtb) for detecting and investigating TB case clusters. Existence of few genomic differences between Mtb isolates might indicate TB cases are the result of recent transmission. However, the variable and sometimes long duration of latent infection, combined with uncertainty in the Mtb mutation rate during latency, can complicate interpretation of WGS results. To estimate the association between infection duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…Furthermore, we showed a relatively high transmission rate (54/88, 61.4%). These results differ from previous local studies where a low transmission rate was reported when using MIRU-VNTR (38,39) or using WGS for the localities of Valencia (24%) (40) and Los Angeles (25%) (41). This could be due to a large percentage of cluster of two isolates (43.8%) in our results or the highest SNPs umbral used in other studies (15 SNPs).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we showed a relatively high transmission rate (54/88, 61.4%). These results differ from previous local studies where a low transmission rate was reported when using MIRU-VNTR (38,39) or using WGS for the localities of Valencia (24%) (40) and Los Angeles (25%) (41). This could be due to a large percentage of cluster of two isolates (43.8%) in our results or the highest SNPs umbral used in other studies (15 SNPs).…”
Section: Discussioncontrasting
confidence: 99%
“…Owing to the low rate of molecular evolution observed in M. bovis, the phylogenetic methods we employ lack the resolution over shorter outbreak time scales to identify such amplification events and inform on their impact. Indeed, this latter point is an even more broadly salient one -it is recognized that it is difficult to elucidate transmission dynamics for monomorphic pathogens with low rates of evolution using genomic data alone [5], as has been noted before for another member of the MTBC, M. tuberculosis [61,78].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, this latter point is an even more broadly salient one – it is recognized that it is difficult to elucidate transmission dynamics for monomorphic pathogens with low rates of evolution using genomic data alone [5], as has been noted before for another member of the MTBC, M. tuberculosis [61, 78].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there has been a trend in the United States to limit LTBI testing by tuberculin skin test or interferon-γ release assay to select high-risk groups ( 117 ). Interestingly, recent work using WGS to address the matter of recent versus remote infection found that longer latency times do not necessarily correlate with SNP distance — a finding that calls into question the reliability of genomic determinants in estimating the recency of infection ( 118 ). Additional studies using high sequencing depth to query M. tuberculosis mutation rates in human patients, particularly during paucibacillary states, may refine the relationship between the rate of M. tuberculosis mutation acquisition and latency time to enhance epidemiological tracking tools.…”
Section: Epidemiologymentioning
confidence: 99%